Large-scale variability in surface bacterial carbon demand and growth efficiency in the subtropical northeast Atlantic Ocean - Alonso-Sáez, Laura; Gasol, Josep M.; Arístegui, Javier; Vilas, Juan C.; Vaqué, Dolors; Duarte, Carlos M.; Agustí, Susana (Limnology and Oceanography, 2007)
We present surface estimates of bacterial respiration, bacterial heterotrophic production (BHP), and bacterial growth efficiency (BGE), and their relationship with nutrient availability, along a trophic gradient from coastal upwelling waters to the open‐ocean waters of the eastern North Atlantic. Bacterial respiration generally ranged between 10 and 30 µg C L−1 d−1 and was relatively unaffected by nutrient enrichment. In contrast, BHP showed higher variability (more than one order‐of‐magnitude range) and was affected by carbon and/or phosphorus additions in different regions. Empirical bacterial carbon‐to‐leucine (Leu) conversion factors (CFs) (range, 0.02–1.29 kg C mol Leu−1) decreased from the coast to the open ocean, largely influencing the BHP estimates in oligotrophic waters. We found high percentages of Leu respiration in oceanic waters (average 68% of Leu taken up by bacteria), possibly related to the low CFs found offshore. Empirical CFs were highly correlated to BGE (Pearson correlation coefficient r = 0.86, n = 12, p < 0.0004, log‐log transformed), which varied between 1% in offshore waters and 56% in the upwelling waters. Empirical CFs could be critical not only for accurately constraining BHP, but probably also for predicting BGE in oceanic waters. 546 533 3,277 Q1 SCIE